Metode TafsÃ®r TarbawÃ® Dalam Tinjauan Teoritis Dan Praktis - Rosidin, Rosidin (J-PAI: Jurnal Pendidikan Agama Islam, 2015)
The Holy Qurâ€™an is a primary resource for Islamic education. Therefore,Â itâ€™s important to fid an appropriate method which enable to research andÂ explore contents of The Holy Qurâ€™an extensively. The writer proposes aÂ TafsÃ®r TarbawÃ® method as an alternative idea. This method is combiningÂ thematic exegesis method (TafsÃ®r MawdlÈ—â€›Ã®) and education approach, especially Islamic education approach. There are steps to apply TafsÃ®rÂ TarbawÃ® method: 1) select a theme; 2) compile verses of Qurâ€™an then classify;Â 3) Tabulate verses according to NuzÈ—l al-Qurâ€™an then know about AsbÃ¢bÂ al-NuzÈ—l and al-MunÃ¢sabah (correlation of verses); 4) Analyze verses by al-TafsÃ®r, al-Sunnah, Ushul al-Fiqh, Islamic education, and every disciplineÂ â€“especially education theoryâ€“ that is much-needed to gain comprehensiveÂ and complete conclusion of this method. Beside theoretical frameworkÂ and TafsÃ®r TarbawÃ® method in pratice, the writer also presents example of this methodâ€™s product entitle: â€œConcept ofÈ–lÈ— al-AlbÃ¢b in Qurâ€™an and itsÂ Implication for Islamic Educationâ€. The result of this example shows aÂ combination of exegesis and Islamic education analysis. Thus, this articleÂ proves that TafsÃ®r TarbawÃ® method could be an appropriate method toÂ discover contents of The Holy Qurâ€™an for developing theory and practiceÂ of Islamic education.